Farmer Participatory Vatidation of Indigenous Technical Knowledge in Agriculture - R.N. Padaria, Baldeo Singh, Jitendra Kumar, B.M. Sharma; M. Pathak (Indian Journal of Extension Education, 2009)
Indigenous technical knowledge has assumed greater significance in search of eco-friendly practices for sustainable agriculture. The present study made an attempt to develop mechanism of participatory validation of the potential of indigenous technical knowledge. Two ITK of managing gundhi bug with exffacts of garlic and tobacco mixed with washing powder and management of termites with lime and salt were subjected to validation vis-d-vis the recommended practices for the respective pest. Though the trials showed better efficacy of recommended practices in comparison to indigenous practices for management of gundhi bug in rice and termite in sugarcane; the participatory on-farm validation trials helped farmers to understand the techniques of field experimentation, data record keeping, analysis and drawing logical conclusions besides attribution process of cause and effect relationship. Dialogue and working with scientists enhanced the confidence of farmers and motivated them to take up experimentation with sound methodology and validate other technologies and own practices with scientific rationality’